Combined head accelerometry and EEG improves the detection of respiratory‐related cortical activity during inspiratory loading in healthy participants. Issue 13 (11th July 2022) - Hudson, Anna L.; Wattiez, Nicolas; Navarro‐Sune, Xavier; Chavez, Mario; Similowski, Thomas
Abstract: Mechanical ventilation is a highly utilized life‐saving tool, particularly in the current era. The use of EEG in a brain–ventilator interface (BVI) to detect respiratory discomfort (due to sub‐optimal ventilator settings) would improve treatment in mechanically ventilated patients. This concept has been realized via development of an EEG covariance‐based classifier that detects respiratory‐related cortical activity associated with respiratory discomfort. The aim of this study was to determine if head movement, detected by an accelerometer, can detect and/or improve the detection of respiratory‐related cortical activity compared to EEG alone. In 25 healthy participants, EEG and acceleration of the head were recorded during loaded and quiet breathing in the seated and lying postures. Detection of respiratory‐related cortical activity using an EEG covariance‐based classifier was improved by inclusion of data from an Accelerometer‐based classifier, i.e. classifier 'Fusion'. In addition, 'smoothed' data over 50s, rather than one 5 s window of EEG/Accelerometer signals, improved detection. Waveform averages of EEG and head acceleration showed the incidence of pre‐inspiratory potentials did not differ between loaded and quiet breathing, but head movement was greater in loaded breathing. This study confirms that compared to event‐related analysis with >5 min of signal acquisition, an EEG‐based classifier is a clinically valuable tool with rapid processing, detection times, and accuracy. Data smoothing would introduce a small delay (<1 min) but improves detection results. As head acceleration improved detection compared to EEG alone, the number of EEG signals required to detect respiratory discomfort with future BVIs could be reduced if head acceleration is included.